THE TRANSLATION TECHNIQUES OF CULTURAL WORDS IN JK ROWLINGâ€™S HARRY POTTER AND THE HALF-BLOOD PRINCE - otniel gerry prizanto; Dwi Aji Prajoko (Humaniora Scientia, 2023)
The aim of this research was to describe cultural words in JK Rowling's novel entitled Harry Potter and The Half-Blood Prince and to analyze their translation techniques of them. The form of the data was language units, namely words, and phrases containing cultural words in the novel. The data were collected with document analysis. The findings were that all types of cultural words were found in Harry Potter and The Half-Blood Prince, namely material culture, habits, organization, ecology, and social culture. The translation techniques that were used are established equivalent, pure borrowing, literal translation, adaptation, generalization, particularization, explicitation, paraphrase, addition, and modulation. The dominant translation techniques are established equivalent and pure borrowing.Â Keywords: Cultural words, translation technique, Harry Potter and The Half-Blood Prince